Primary adenocarcinoma of the fallopian tube mimicking pelvic inflammatory disease. - Tamby, MR; Juliana, MB; Wan Hamilton, WH; Hemlata, KG; Masir, N (Penerbit UKM, 2011)
Primary fallopian tube carcinomas are rare and are difficult to diagnose preoperatively. We describe a fallopian tube carcinoma in a 50-year-old lady who presented with symptoms of pelvic inflammatory disease. Ultrasound examination showed bilateral hydrosalphinx. However, CT scan showed features suggestive of a malignant ovarian tumour. At surgery, a markedly dilated left fallopian tube was found and histopathological examination confirmed the presence of a primary serous adenocarcinoma. The uterus and both ovaries were free of tumour. This report highlights that carcinoma of the fallopian tube should be considered as a differential diagnosis in females who present with lower abdominal pain.